STRATEGI DINAS PERHUBUNGAN KOTA SEMARANG DALAM MENERTIBKAN PARKIR LIAR TEPI JALAN UMUM DI KAWASAN SIMPANG LIMA - Kamelia Fadila Wijaya; Aufarul Marom; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The problem of illegal parking in the Simpang Lima area is a serious problem faced by the City Government of Semarang. Simpang Lima is the heart of Semarang City and is the meeting point of five roads that unite. The problem that is often encountered is the large number of vehicle users who do not park their vehicles in the places provided by the government, as well as the many complaints regarding the collection of parking fees that are not in accordance with Mayor Regulation Number 9 of 2018 regarding public roadside parking fees. The purpose of this study is to analyze the internal and external environment of the Semarang City Transportation Service in controlling illegal public roadside parking in the Simpang Lima area, identify strategic issues, and formulate strategies to manage these issues. The research method used in this study is descriptive qualitative using primary data sources obtained through interviews and field observations as well as secondary data. In this study, researchers used SWOT analysis and Litmus tests as instruments to formulate the strategy needed to control illegal parking on public roads in the Simpang Lima area. The results of the study show that controlling illegal parking on the side of public roads in the Simpang Lima area cannot be said to be optimal, so a strategy is needed to reduce illegal parking and illegal parking attendants. The recommended and most strategic strategy is to implement electronic parking at several parking points in the Simpang Lima area. The aim of this strategy is to minimize illegal levies and increase local revenue both from parking taxes and parking fees.